Prediction Of Blast-Induced Ground Vibration During Blasting At Lafarge Quarry Kanthan, Ipoh, Perak - Pelawang, Khairul Shazwan (Universiti Sains Malaysia, 2018)
Blasting works give impacts toward environment due to waste-energy produced from blasting such as ground vibration, air blast and fly rock. Effects of ground vibration to environment including damage of structure and annoyance of human. Study was conducted at Lafarge Quarry, Kanthan, Perak to study ground vibration and its relationship in the quarry. A new predictor will be used to predict ground vibration. During the blasting, value of site constants k and β will be determined in predicting the ground vibration. To construct the model of predictor, a few parameters will be taken into account such as distance between blast point and monitoring point, maximum amount of charge per delay and blast design. Besides that, peak particle velocity (PPV) also will be analysed. The relationship between these parameters with peak particle velocity (PPV) will determined the site constant value k and β. Laboratory work such as point load test index and uniaxial compressive strength (UCS) will be applied. A new established prediction in Lafarge Kanthan is PPV = 2448 (D/√Q)-1.7 with value of R 2 = 0.9604 which indicate the correlation are valid between scaled distance and ground vibration produced. The new predictor is more accurate compare to the existing practices that used the Australian Standard (A.S. 2187, 1993) which practiced by most quarry operators in Malaysia.